Texas abduction - Han, Barb (Han, Barb. O'Connor family mystery., 2021)
Texas rancher Riggs O'Connor and his estranged wife Cheyenne O'Connor come together to solve the mysteries surrounding Cheyenne's missing friend as well as their young daughter they both believed passed away at birth.